Exploring Televend, an innovative combination of cryptomarket and messaging app technologies for trading prohibited drugs - Barratt M.J. (2023)
Background: Digital technologies continue to facilitate drug trading. Televend was an innovative combination of multiple digital technologies, with its backend hosted on the darknet, while purchases were made through the messaging app Telegram. Here, we provide an initial characterisation of this nascent market. Methods: Televend and White House Market (WHM) were scraped (Jun–Jul 2021) and a global cross-sectional web survey of 15,513 drug buyers (Global Drug Survey; GDS) was conducted (Dec 2020–Mar 2021). Results: Televend was 10% of the size of WHM, the largest drug cryptomarket (4515/44,830 listings per week). Both markets predominantly contained drug-related listings covering similar drug categories, with similar country of origin and destination. Very few GDS drug buyers reported use of Televend (0.73%). Most Televend buyers (68/114) reported buying cannabis, then cocaine (20), MDMA (17), and LSD (12). The Televend and darknet groups had similar demographic and drug use characteristics; whereas compared with app purchasers, older age increased the odds of Televend use (aRRR = 1.06, p < .001), identifying as a cisgender woman decreased the odds (aRRR=0.43, p = .004), while last-year use of a greater number of drug types (aRRR = 1.20, p < .001) and less frequent drug use (aRRR=0.998, p = .032) increased the odds of Televend purchase. Conclusions: While smaller, Televend was not noticeably different in its drug offerings to its largest cryptomarket competitor, and it attracted a cohort more similar to darknet than to app drug buyers. Future Televend-like markets may be attractive to people with less specialised technical knowledge who already routinely scroll through social media feeds.